2020
DOI: 10.3390/pharmaceutics12111060
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the In Vitro and Ex Vivo Permeation of Existing Topical Formulations Used in the Treatment of Facial Angiofibroma and Characterization of the Variations Observed

Abstract: Rapamycin has been used topically to treat facial angiofibromas associated with tuberous sclerosis for more than a decade. In the absence of a commercial form, a large number of formulations have been clinically tested. However, given the great heterogeneity of these studies, particularly with regard to the response criteria, it was difficult to know the impact and thus to compare the relevance of the formulations used. The objective of this work was therefore to evaluate the link between the diffusion of rapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…In the case of IVPT, to analyze data, QT amount permeated (μg/cm 2 ) was plotted as a function of time. Fick’s law was considered since it describes the steady-state permeation through the skin, assuming that, under sink conditions, drug concentration in the receptor compartment is negligible with respect to that in the donor compartment [ 35 ]. The steady-state flux of drug per unit area “Jss” is described as: Jss = P × Cd × D/e where P is the partition coefficient, Cd is the drug concentration in the donor compartment, D is QT diffusion coefficient, and e is the thickness given by the supplier or measured.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of IVPT, to analyze data, QT amount permeated (μg/cm 2 ) was plotted as a function of time. Fick’s law was considered since it describes the steady-state permeation through the skin, assuming that, under sink conditions, drug concentration in the receptor compartment is negligible with respect to that in the donor compartment [ 35 ]. The steady-state flux of drug per unit area “Jss” is described as: Jss = P × Cd × D/e where P is the partition coefficient, Cd is the drug concentration in the donor compartment, D is QT diffusion coefficient, and e is the thickness given by the supplier or measured.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were analyzed using the HPLC method to determine the amount of rapamycin diffused. The steady state flux at 24 h, in vitro skin permeation steady state flux (Jss) (µg cm −2 h −1 ), was determined by measuring the slope from the plot of the cumulative amount permeated versus time [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…The epidermis was subsequently separated from the dermis, and each compartment was cut into small pieces and soaked in methanol for 12 h with continuous stirring at room temperature. The extraction procedure was validated in our previous study (data not shown) [ 11 ]. The extraction skin samples were then centrifuged at 10,000 rpm for 15 min and analyzed by HPLC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The permeation coefficient (Kp; the speed of the drug track across the membrane in cm/h) was computed with the equation Kp = Jss/Co, where Jss is the flux and Co is the donor solution concentration [ 47 ]. The diffusion coefficient (D) was calculated from the lag time (Tlag) with the following equation [ 48 ]: where e was the thickness, controlled and given by the supplier (thickness 5 mm).…”
Section: Methodsmentioning
confidence: 99%